HUBUNGAN DAYA TAHAN KARDIOVASKULER DAN DAYA LEDAK OTOT TUNGKAI DENGAN KEMAMPUAN TENDANGAN DEPAN PADA ATLET PUTRA PERGURUAN WALET PUTI CABANG PEKANBARU - Muhammad azhari; Ramadi '; Aref vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: problem whith athletes in the game found that the ability of the front kick iss stil slow and has no power while doingit, and if it kicks repeatedly then the kick is getting weaker and less directed. This reseach is a im to know the correlation of Cardiovascular Endurance between explosive power of legs with Capability Of The Front Kick on the men athletes of walet puti institution pekanbaru. the form of this research is the correlation study, the population in this research are the athletes of walet puti institution pekanbaru, and the sample in this research is consist of ten athletes in walet puti institusion pekanbaru. the calculation of the first analysis between Cardiovascular Endurance (x1) and Capability Of The Front Kick(y) where rresult (-0,120 a second analysis of the correlation between explosive power of legs (x2) andCapability Of The Front Kick (y), where rresult (0,135 the analysis of three correlation of Cardiovascular Endurance(x1) and explosive power of legs (x2) with Capability Of The Front Kick(y), where rresult (0,144) which mean the hypothesis is be accepted and there is a middle correlation of Cardiovascular Enduranceexplosive and power of legs with Capability Of The Front KickKeywords: Cardiovascular Endurance, Explosive Power Of Legs, Capability Of The Front Kick